2020
DOI: 10.3390/en13205467
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Regional Innovation Capability on the Green Technology Efficiency of China’s Manufacturing Industry: Evidence from Listed Companies

Abstract: The purpose of the “Made in China 2025” strategy is to enhance the innovation capabilities of the local manufacturing industry and achieve green and sustainable development. The role of innovation in the development of manufacturing is a hotspot in academic research, though only a few studies have analyzed the interaction between green technology manufacturing efficiency and its external innovation capabilities. This study used the 2011–2017 Chinese A-share listed manufacturing companies as samples to discuss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 48 publications
0
34
0
1
Order By: Relevance
“…Under such circumstances, enterprises hope to establish long-term cooperation with suppliers that provide green raw materials and intermediate products, which in turn improve green innovation performance by providing customers with green products and services. Fu et al [59] pointed out that regional innovation capability can promote the improvement of green technology manufacturing efficiency in China. Based on the data from Chinese listed firms, Xu et al [60] found that R&D investment has a positive impact on green innovation performance.…”
Section: Ic and Green Innovation Performancementioning
confidence: 99%
“…Under such circumstances, enterprises hope to establish long-term cooperation with suppliers that provide green raw materials and intermediate products, which in turn improve green innovation performance by providing customers with green products and services. Fu et al [59] pointed out that regional innovation capability can promote the improvement of green technology manufacturing efficiency in China. Based on the data from Chinese listed firms, Xu et al [60] found that R&D investment has a positive impact on green innovation performance.…”
Section: Ic and Green Innovation Performancementioning
confidence: 99%
“…Empirical investigations in the EU have showed that the green economy can effectively create new sources of growth, providing solutions to environmental problems [11][12][13]. However, the green economy has complex impacts on local development: even in case of industries which seem to take an immediate and direct advantage of green economy policies (such as tourism and agriculture), on closer analysis, a positive impact is possible only when the local economic and government bodies are involved in the change towards the green economy [14][15][16][17][18]. These difficulties increase when sustainability is evaluated according to a multi-dimensional approach (as in the case of the EU definition, which relies on economic, environmental, and social dimensions), as recognized in the literature [19].…”
Section: Introductionmentioning
confidence: 99%
“…e distribution pattern of industrial technology innovation efficiency and the influencing factors of industrial green innovation efficiency, such as industry scale, structure, and government, are studied, and the measures of how to promote industrial green innovation efficiency are clarified [12][13][14]. In addition, relevant studies are distributed to study the role of intermediaries [15] in green technology innovation in terms of methods, and existing studies mostly use empirical data studies [16][17][18].…”
Section: Introductionmentioning
confidence: 99%